2018
DOI: 10.1021/acs.macromol.8b01158
|View full text |Cite
|
Sign up to set email alerts
|

Two Robust Strategies toward Hydrogels from Quenched Block Copolymer Nanofibrillar Micelles

Abstract: While the formation of (tri)block copolymer hydrogels has been extensively investigated, such studies mostly focused on equilibrium self-assembling whereas the use of preformed structures as building blocks such as out of equilibrium, quenched, nanofibrillar micelles is still a challenge. Here, we demonstrate that quenched, ultralong polystyrene-b-poly(ethylene oxide) (PS-b-PEO) micelles can be used as robust precursors of hydrogels. Two cross-linking strategies, (i) thermal fusion of micellar cores and (ii) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
5
1
Order By: Relevance
“…Our system is different from the previous studies because the sticky gel that contains PS 317 -b-PEO 307 in the THF/water (1/0.22) cosolvent does not display the prominent features corresponding to the scattering of core–shell micelles. Instead, a Bragg peak is displayed, together with power-law intensity decays.…”
Section: Resultscontrasting
confidence: 64%
See 2 more Smart Citations
“…Our system is different from the previous studies because the sticky gel that contains PS 317 -b-PEO 307 in the THF/water (1/0.22) cosolvent does not display the prominent features corresponding to the scattering of core–shell micelles. Instead, a Bragg peak is displayed, together with power-law intensity decays.…”
Section: Resultscontrasting
confidence: 64%
“…The aggregation of the patchy micelles usually forms fractal networks, which further freezes the liquid. In fact, patchy micelles of various morphologies are frequently reported . Similar to fractal networks of patchy micelles, fibrillar networks (also called worm-like micelles or branched cylinders) are frequently obtained for gels or viscous solutions. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that with the aim of immobilizing the micelles on DexMA hydrogel, the PS-b-PEO micelles used here were partially functionalized with methacrylate (denoted as PS-b-PEO(MA)) through ac o-assembly approach. [17] Briefly,amixture of methacrylated PS-b-PEO block copolymers (PS-b-PEO-MA) and pristine PS-b-PEO block copolymers was used in the evaporation-induced self-assembly process.T hrough copolymerization with DexMA in the laser illuminated region (Figure 1c-2), PS-b-PEO(MA) micelles were capable of bonding onto DexMA hydrogel. This was confirmed by the formation of ahybrid structure that micellar filaments were embedded on the surface of hydrogels (Figure 1c-3).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Furthermore, it has been shown that quenched micelles, containing a glassy core, exhibit such a length without branching. Zhang et al [27] presented such micelles, with lengths of up to 250 μm. The amphiphilic nature of the building blocks opens up many options when it comes to integration of different molecules into the core while keeping the solubility in a solvent unimpeded.…”
Section: Randomly-aligned Nanowiresmentioning
confidence: 99%